The relationships between rugby union, and health and well-being: a scoping review - Griffin, S. A.; Perera, N. K. P.; Murray, A.; Hartley, C.; Fawkner, S. G.; Kemp, S. P. T.; Stokes, K. A.; Kelly, P. (British Journal of Sports Medicine, 2021)
Objective: To scope the relationships between rugby union, and health and well-being. Design: Scoping review. Data sources: Published and unpublished reports of any age, identified by searching electronic databases, platforms and reference lists. Methods: A three-step search strategy identified relevant published primary, secondary studies and grey literature, which were screened using a priori inclusion criteria. Data were extracted using a standardised tool, to form a numerical analysis and a thematic summary. Results and discussion: 6658 records were identified,and 198 studies met the inclusion criteria. All forms of rugby union can provide health-enhancing physical activity (PA). `Non-contact` and wheelchair rugby in particular provide a wide range of physical and mental health and well-being benefits. The evidence is either mixed or unclear in relation to `contact` rugby union and its effects on a range of physical health domains. Injury and concussion incidence rates are high for contact rugby union relative to other sports. Conclusions: A wide range of stakeholders as well as existing and potential participants can use this information to make a more informed decision about participating in and promoting rugby union as a health-enhancing activity. Industry and policy-makers can use this review to inform policies and strategies that look to increase participation rates and use rugby union as a vehicle to contribute positively to population health. Further research understanding rugby union`s contribution to PA as well as to muscle-strengthening and balance is indicated, as well as research examining more health and well-being outcomes across more diverse cohorts.